At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Given the algebraic equation
[tex]v^2-12v+28=-7[/tex]We are asked to solve the question using the completing the square method. This can be done with the following steps
Explanation
Step 1: Take all the constant to the right hand side
[tex]\begin{gathered} v^2-12v+28=-7 \\ v^2-12v=-7-28 \\ v^2-12v=-35 \end{gathered}[/tex]Step 2: Add to both sides the square of half the coefficient of x
[tex]\begin{gathered} v^2-12v+(-\frac{12}{2})^2=-35+(-\frac{12}{2})^2 \\ \end{gathered}[/tex]Step 3: Factorize the left-hand sign and simplify the right-hand side.
[tex]\begin{gathered} v^2-12v+(-\frac{12}{2})^2=-35+(-\frac{12}{2})^2 \\ v^2-12v+6^2=-35+6^2 \\ (v-6)^2=1 \end{gathered}[/tex]Step 4: Find the square root of both sides
[tex]\begin{gathered} \sqrt[]{(v-6)^2}=1 \\ v-6=\pm\sqrt[]{1} \\ v=6\pm\sqrt[]{1} \end{gathered}[/tex]The solution to the equation is
Answer:
[tex]v=7,\: v=5[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.